2020
DOI: 10.2147/jpr.s255221
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Interaction Between Spinal PDGFRβ and μ Opioid Receptor in the Activation of Microglia in Morphine-Tolerant Rats</p>

Abstract: Purpose: Opioid tolerance remains a challenging problem, which limits prolonged drug usage in clinics. Previous studies have shown a fundamental role of platelet-derived growth factor receptor β submit (PDGFRβ) in morphine tolerance. The aim of this study was to investigate the mechanisms of spinal PDGFRβ activation in morphine tolerance. Methods: Rats were treated with morphine for 7 days and the effect of drug was evaluated by tail-flick latency test. By using Western blot and real-time PCR, the interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Putative roles for RTK signaling in opioid tolerance were first shown in mice with global deletion of EphRB1 ( Liu et al, 2011 ) as they failed to develop tolerance to spinal morphine administration. Similarly, we and others found that systemic or intrathecal co-administration of morphine alongside RTK inhibition via inhibitors of PDGFRβ ( Wang et al, 2012 ; Li et al, 2020 ; Puig et al, 2020a ), EGFR ( Puig et al, 2020b ), or VEGFR-2 ( Lopez-Bellido et al, 2019 ) completely blocked tolerance. Together, these studies show that spinal RTK signaling is essential in morphine tolerance development.…”
Section: Involvement Of Receptor Tyrosine Kinase Signaling Opioid-med...supporting
confidence: 72%
See 2 more Smart Citations
“…Putative roles for RTK signaling in opioid tolerance were first shown in mice with global deletion of EphRB1 ( Liu et al, 2011 ) as they failed to develop tolerance to spinal morphine administration. Similarly, we and others found that systemic or intrathecal co-administration of morphine alongside RTK inhibition via inhibitors of PDGFRβ ( Wang et al, 2012 ; Li et al, 2020 ; Puig et al, 2020a ), EGFR ( Puig et al, 2020b ), or VEGFR-2 ( Lopez-Bellido et al, 2019 ) completely blocked tolerance. Together, these studies show that spinal RTK signaling is essential in morphine tolerance development.…”
Section: Involvement Of Receptor Tyrosine Kinase Signaling Opioid-med...supporting
confidence: 72%
“…Fujita-Hamabe et al, 2011Blackwood et al, 2019 Platelet-derived growth factor receptor (PGFR) Wang et al, 2012;Weber et al, 2013;Li et al, 2020Wang et al, 2012Puig and Gutstein, 2017;Puig et al, 2020aNarita et al, 2005Donica et al, 2014 Insulin Receptor (IR) Mclaughlin and Chavkin, 2001;Li et al, 2003Li et al, 2003Xu et al, 2012Ephrin B Liu et al, 2011Liu et al, 2011Han et al, 2008Xia et al, 2014 Tyrosine receptor kinase B (TrkB) Peregud et al, 2016;Rezamohammadi et al, 2020Freeman et al, 2003Koo et al, 2012;Koo et al, 2014;Jorjani et al, 2021 Fms-like tyrosine kinase (FLT3) (PI3K), mitogen-activated protein kinase/p38 (MAPK/p38), Ras-GTPase-activating protein (Ras-GAP), Janus kinase/signal transducer and activator of transcription (JAK/STAT), protooncogene c-Src, or focal adhesion kinase (FAK) signaling cascades (for a review see: (Lemmon and Schlessinger, 2010;Du and Lovly, 2018). Historically, RTK signaling pathways were found to be involved in cell proliferation, differentiation, migration, or metabolic changes (Lemmon and Schlessinger, 2010), and were also associated with cancer development (Du and Lovly, 2018).…”
Section: Opioid Rewardmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found that opioids given during development drastically reduce microglial process branching and hence the overall size and complexity of microglia; morphological changes indicative of microglial activation 9 . Other studies found that microglial activation is increased in a model of chronic morphine administration but can be reduced by the non-specific opioid receptor antagonist, Naloxone 70 , 71 . The effect of Bup on the immune system is not fully understood, but there is likely an interplay between its roles as a partial agonist at the MOR and antagonistic properties toward the other opioid receptors.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies found that opioids given during development drastically reduce microglial process branching and hence the overall size and complexity of microglia; morphological changes indicative of microglial activation 9 . Other studies found that microglial activation is increased in a model of chronic morphine administration but can be reduced by the non-speci c opioid receptor antagonist, Naloxone 70,71 . The effect of Bup on the immune system is not fully understood, but there is likely an interplay between its roles as a partial agonist at the MOR and antagonistic properties toward the other opioid receptors.…”
Section: Discussionmentioning
confidence: 96%